Political and Public Acceptability of Congestion Pricing: Ideology and Self Interest - Bjorn Harsman; John Quigley (European Regional Science Association (ERSA), 2010)
Studies of the "stated preferences" of households generally report public and political opposition by urban commuters to congestion pricing. It is thought that this opposition inhibits or precludes tolls and pricing systems that would enhance efficiency in the use of scarce roadways. This paper analyzes the only case in which road pricing was decided by a citizen referendum on the basis of experience with a specific pricing system. The city of Stockholm introduced a toll system for seven months in 2006, after which citizens voted on its permanent adoption. We match precinct voting records to citizen commute times and costs by traffic zone, and we analyze patterns of voting in response to economic and political incentives. We document political and ideological incentives for citizen choice, but we also find that the pattern of time savings and incremental costs exerts a powerful influence on voting behavior. In this instance, at least, citizen voters behave as if they value commute time highly. When they have experienced first-hand the out-of-pocket costs and time-savings of a specific pricing scheme, they are prepared to adopt freely policies which reduce congestion on urban motorways.
Keywords: R41; R48; Q58; 330; highway tolls; voting behavior; commuting costs